1994
DOI: 10.1016/s0741-5214(94)70216-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of paraplegia during thoracic aortic cross-clamping: Importance of patent internal mammary arteries

Abstract: Unexplained anatomic and physiologic factors account for the unacceptably high rate of paraplegia/paresis after thoracoabdominal aortic reconstruction. We assessed the neurologic significance of patent internal mammary arteries (!MAs) in a hovel rat model of aortic clamping in which the aortic origins of the intercostal arteries (ICAs) were occluded. Methods: Twenty anesthetized, intubated, and halothane-ventilated adult male rats had catheters placed in the carotid and femoral arteries. ICAs arising from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…2,28 Experimentally, even direct perfusion of the arteria radicularis magna (artery of Adamkiewicz) during aortic occlusion with reperfusion of all intercostals has no protective effect. 29 There is also strong experimental evidence that collateral blood flow during aortic occlusion is an important factor in cord preservation 30 and that chemical or mechanical shunting of blood away from the cord collaterals (especially the upper thoracic intercostals) has a significant negative effect on spinal cord viability. 31,32 Our paraplegia risk model analysis of clinical reports strongly implies that intercostal reimplantation during aortic occlusion offers no protection from paraplegia, with or without assisted circulation.…”
Section: Discussionmentioning
confidence: 99%
“…2,28 Experimentally, even direct perfusion of the arteria radicularis magna (artery of Adamkiewicz) during aortic occlusion with reperfusion of all intercostals has no protective effect. 29 There is also strong experimental evidence that collateral blood flow during aortic occlusion is an important factor in cord preservation 30 and that chemical or mechanical shunting of blood away from the cord collaterals (especially the upper thoracic intercostals) has a significant negative effect on spinal cord viability. 31,32 Our paraplegia risk model analysis of clinical reports strongly implies that intercostal reimplantation during aortic occlusion offers no protection from paraplegia, with or without assisted circulation.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the patency of all spinal cord collaterals preoperatively, such as the bilateral subclavian arteries, vertebral arteries, internal thoracic arteries, and internal iliac arteries, and we performed a right axillary-to-left axillary arterial bypass to preserve LSCA blood flow. Several studies have reported the importance of preserving these collateral arteries to prevent spinal cord ischemia, 46 but due to insufficient findings, the evidence has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…The cervicodorsal region of the spinal cord is, in fact, supplied also by branches of the costocervical trunk, and by the occipital, deep cervical, and ascending cervical arteries (6). The collateral circulation to the mid-thoracic and thoracolumbar regions of the spinal cord is provided by the intercostal and lumbar vessels and Giglia et al (23), in an experimental rat model, observed that also the internal mammary arteries are important collateral circulation contributors. Christiansson et al (20), interestingly, showed that collateral circulation through proximal feeding vessels such as vertebral arteries and supreme intercostal arteries is prevented by clamping the subclavian arteries and ligating the mammary arteries.…”
Section: Spinal Cord Blood Supplymentioning
confidence: 99%